Pengaruh Good Corporate Governance Dan Profitabilitas Terhadap Nilai Perusahaan - Lembah Dewi Andini; Fransiska Olga Ajim; Fatah Ladava Cahya Agung (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This research examines the effect of good corporate governance and profitability on value company. Good corporate governance is measured using the Managerial Ownership formula and profitability using the Return on Assets formula.The composition of company values uses the Tobin's Q formula to analyze the financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. Based on the partial test results of the 5 sampled companies, it shows that the good corporate governance variable has a negative effect, while the profitability variable has a positive on value company.